Community structure and trophic ecology of shallow and deep rocky reefs in a well-established marine protected area - Heyns, Elodie R (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2016)
The now formally adopted ecosystem approach to fisheries (EAF) considers not only commercially important species, but the entire ecosystem and the processes that support these species. A key component of EAF management is the implementation of no-take Marine Protected Areas (MPAs). Shallow water fish stocks are depleted and fishing effort is moving deeper and further offshore to keep up with demands. This situation calls for a detailed investigation of deep nearshore reefs to provide critical information relevant to policy uptake and management decisions regarding existing and new MPAs in terms of zonation and use. To address this need, the aim of this thesis was to investigate reefs that lie between 45 and 75 m and compare them in terms of community structure and function to the relatively well-studied shallow reefs that lie within SCUBA diving depth (<25 m). Ecological collections were made in the centre of a large and well-established MPA, Tsitsikamma National Park, to ensure that data represented non-anthropogenically impacted communities. Data were collected from two study sites; Rheeders Reef, (shallow reef) and Middlebank, a deep reef complex situated near the Storms River Mouth. The first step to address the aim of this study was to obtain baseline data on the distribution patterns of both the macrobenthic invertebrates and fish assemblages. Baseline data were obtained by underwater video methods and included the use of a remotely operated vehicle, baited remote underwater stereo-video systems (stereo-BRUVs) and traditional underwater camera equipment operated by SCUBA divers. To establish functional differences between the two study sites, fatty acid (FA) and stable isotope (SI) analyses were employed. These biomarker techniques provided insight into the importance of different sources of primary production, nutritional condition and species packing. From 360 photoquadrats examined for macrobenthic invertebrate distribution patterns, 161 invertebrates were identified that demonstrated a clear changeover of species along the depth gradient. Species richness was highest on the shallow reef and decreased with an increase in depth. To understand how the measured environmental variables impacted the macrobenthic assemblage data a LINKTREE analysis was performed. LINKTREEs produce hierarchical cluster analysis based on the macrobenthic assemblage data and provide a threshold of environmental variables that correspond to each cluster. The outcome of the LINKTREE analysis indicated that the changeover of species resulted in four distinct clusters, each cluster associated with a particular set of environmental variables that fell within a depth range. On the shallowest sites, the high energy environment resulting from wave action and surge prevented the settlement of suspended particles. The high energy environment of the shallow reef selected for low-growing encrusting species. High light intensities supported great abundances of benthic algae, and as light was lost with increasing depth, algal cover gradually diminished until it was completely absent on the deep reef. The reduced impact of surface wave action on the deep reef caused increased levels of settled suspended particles. The high levels of settled particles likely caused clogging of feeding parts of the encrusting species. Consequently, upright growth forms were more common in the lower energy environment of the deep reef. A total of 48 fish species were identified from 51 stereo-BRUVs samples. Fish assemblages differed significantly between the shallow and deep reefs. The shallowest sites were characterised by many small and juvenile fish species that fed at lower trophic levels. The deep reef supported the majority of the large predatory fish that fed at higher trophic levels. Many species demonstrated depth-related ontogenetic shifts in habitat use, and as such the deep reef hosted the majority of the sexually mature individuals. The fish assemblages also demonstrated a strong association with the macrobenthic clusters identified as habitat types by the LINKTREE analysis. The results from 201 FA and 191 SI samples provided information on specific feeding interactions, but more importantly shed some light on different processes that supported the shallow and deep reef communities. The shallow reef community was characterised by greater diversity of food sources, a pattern that could be explained by the presence of benthic algae and terrestrial inputs. Greater diversity of carbon sources at the bottom of the food web meant that a larger variety of species could be supported. Higher species richness increased the number of distinct taxa that performed similar functions, rendering the shallow reef more redundant and consequently more resilient to disturbance. In contrast, the deep reef demonstrated a food web supported mainly by pelagic production, which was more variable both over space and time. The deep reef was less redundant when compared to the shallow reef, as fewer species demonstrated similar trophic niches. These factors, in addition to the increased presence of sensitive calcareous macrobenthic species on the deep study site, rendered the deep reef more vulnerable to disturbance when compared to the shallow reef. Although the data presented here were from a single study area, the limitations typically associated with these inaccessible and challenging sampling environments made the dataset a significant contribution to the knowledge of reef ecosystems. The study addressed priority research questions for South Africa as identified during the National Biodiversity Assessment. The observable differences in structure, function and vulnerability point to the need for continued protection of our shallow reefs and offshore expansion of our MPA networks. Future research should determine if the patterns identified here are common throughout the Agulhas Ecoregion to provide managers with robust evidence for the extension our MPAs offshore.
Keywords: Uncatalogued